Influencia del tráfico vehicular en los niveles de inmisión de ruidos en la ciudad de Juanjui – departamento de San Martín - Rengifo Pinedo, Karen (2011)
This paper entitled "Influence of Vehicular Traffic on Noise emissiori levels in the City of Juanjuí - San Martín 2011." It was developed in the city of Juanjuí, aiming determines the influence of vehicular traffic on noise emission levels in the city of Juanjuí- San Martín 2011. The research is descriptive sample was taken as eight monitoring points, located at strategic points in the city, selected at random in the main points of concentration and times 6:30 to 7:30 a.m., 12:00 - 1:00 pm, 5:30 to 6:30 pm. Reached the following conclusions: There has been calculating the amount of vehicles on the main streets of the city of Juanjuí, finding that the number of vehicles per hour in larger quantities, is presented in Tatters, Jr. Arica Intersection with Huallaga, (31 0.8 motor units), Jr. intersection point with the Triunfo (324.71 motorized units) and the intersection with La Merced Jr . . Huallaga ( 417.63 motorized units ), respective! y. It also has been identified that the mobile unit is more frequent are the Motokar transitavililad, followed by linear motorcycles. Juanjuí vehicle fleet is increasing considerably, for, considering that the arteries are very narrow circulation creating many problems of congestion, especially during peak hours. So we can confirm that the increased number of vehicles in any city in the world, contributes to the deterioration of the quality of life and air pollution of present a.•1d future generations It has succeeded in measuring the noise emission levels in the city of Juanjuí, finding points N o 3 (Intersection with Jr. Arica and Huallaga) and item No. 5 (Punta Intersection Jr. win), it provides the highest levels of noise in three shifts. Also it can be concluded that the values measured at all monitoring points, exceeds Environmental Quality Standards for the daytime,. both for residential, commercial and industrial, having obtained values from 70.49 and 95.59 dB. Not found a direct relationship between the number ofvehicles in the city of Juanjuí and noise emission levels, given that the monitoring points are not necessarily the greatest proportion of vehicles there is a higher level of noise.